Comparison of three interactive video games for youth with visual impairments. (January 2018) - Gasperetti, Barbara A; Foley, John T; Yang, Stephen; Columna, Luis; Lieberman, Lauren J
There is a current trend toward using innovative interventions, such as active video gaming to increase physical activity levels among youth with visual impairments. Therefore, the purpose of this study was to compare three video games (Dance, Dance, Revolution [DDR]; EyeToy Kinetic; and Wii Boxing) in allowing youth with visual impairments to achieve time (seconds spent during a 10-min bout) in moderate-to-vigorous physical activity (MVPA). Participants with complete data were youth ( N = 5) with visual impairments aged 10–16 years who played three games for 10-min bouts. Heart rate monitors measured physical activity intensity. A Friedman's analysis of variance (ANOVA) was used to determine differences between the three interactive video games. Most players were able to achieve time in MVPA in all three games and there was a significant difference in time spent in MVPA, χ 2 (2) = 7.4, p = .024, with the most time in MVPA from playing EyeToy Kinetic. This study demonstrated that EyeToy Kinetic, Wii Boxing, and DDR are capable of helping youth with visual impairments accrue time in MVPA.